New Contributions to the Diversity of Hypotrichous Ciliates: Description of a New Genus and Two New Species (Protozoa, Ciliophora) - Ma, Jiyang; Zhang, Tengyue; Song, Weibo; Shao, Chen (Frontiers in Microbiology, 2021)
Ciliated protists (ciliates) are extremely diverse and play important ecological roles in almost all kinds of habitats. In this study, two new hypotrichs, Wilbertophrya sinica n. g., n. sp. and Bakuella xianensis n. sp., from China are investigated. Wilbertophrya n. g. can be separated from related genera mainly by the combination of lacking a buccal cirrus, pretransverse cirri and caudal cirri, while possessing frontoterminal cirri. Analyses based on morphological and molecular data confirm the validity of the species, Wilbertophrya sinica n. sp., which is characterized as follows: body 50–115 µm × 15–35 µm in vivo; midventral complex comprises four or five cirral pairs only and terminates above mid-body; three frontal, two frontoterminal cirri, and two to four transverse cirri; about 15 macronuclear nodules; colourless cortical granules sparsely distributed. Another new species, Bakuella xianensis n. sp., was isolated from a freshwater wetland and is defined as follows: body 115–150 μm × 40–65 μm in vivo; about 70 macronuclear nodules; dark-brownish cortical granules in groups; midventral complex comprises 8–12 cirral pairs forming a row that terminates posteriorly in mid-body region and two or three short midventral rows that are continuous with the row of midventral pairs; three frontal, four to six frontoterminal and three to five fine transverse cirri; three bipolar dorsal kineties. Phylogenetic analyses based on SSU rDNA sequence data suggest that the new genus Wilbertophrya n. g. belongs to an isolated clade which might represent an undescribed taxon at family level, whereas Bakuella xianensis n. sp. groups with several congeners and members of other related genera within the core urostylids.